The Effect of Self Efficacy and Work Environment on Employee Performance at PT. Tirta Marwah Mandiri - Wardana, Ema; Kusdarinto, Indra; Mustafa, Sri Wahyuni (PT. EQUATOR SINAR AKADEMIA, 2025)
This study aims to examine the effect of self-efficacy and work environment on employee performance. The population of this study was all employees of PT. Tirta Marwah Mandiri totaling 31 people, and all members of the population were sampled. This study uses a quantitative approach with primary data collected through offline questionnaire distribution. Data analysis techniques include instrument testing, multiple linear regression testing, and hypothesis testing analyzed using the SPSS 26 application. The results of the t-test indicate that self-efficacy has a positive and significant effect on employee performance, as well as the work environment. Meanwhile, the f-test shows that simultaneously, self-efficacy and work environment have a positive and significant effect on employee performance.